Current Scientific Impact of Ss Cyril and Methodius University of Skopje, Republic of Macedonia in the Scopus Database (1960-2014) - Spiroski, Mirko (Open Access Maced J Med Sci, 2015)
AIM: The aim of this study was to analyze current scientific impact of Ss Cyril and Methodius University of Skopje, Republic of Macedonia in the Scopus Database (1960-2014). MATERIAL AND METHODS: Affiliation search of the Scopus database was performed on November 23, 2014 in order to identify published papers from the Ss Cyril and Methodius University of Skopje (UC&M), Republic of Macedonia. A total number of 3960 articles (3055 articles from UC&M, 861 articles from Faculty of Medicine, UC&M, and 144 articles from Faculty of Pharmacy, UC&M) were selected for analysis (1960-2014). SCImago Journal Rank (SJR), Source Normalized Impact per Paper (SNIP) and h-index were calculated from the Scopus database. RESULTS: The number of published papers was sharply increased with maximum of 379 papers in 2012 year. The largest number of papers has been published in Macedonian Journal of Medical Sciences, Journal of Molecular Structure, Lecture Notes in Computer Science, Acta Pharmecutica, and Macedonian Journal of Chemistry and Chemical Engineering. The biggest SJR and SNIP has journal Nephrology Dialysis Transplantation. First three places of the top ten authors belong to Dimirovski GM, Gavrilovska L, and Gusev M. Top three places based on Scopus h-index (total number of published papers) belong to Kocarev L, Stafilov T, and Polenakovic M. The majority of papers originate from UC&M, but significant numbers of papers are affiliated to Faculty of Medicine, Faculty of Pharmacy, and Institute of Chemistry as members of UC&M, as well as Macedonian Academy of Sciences and Arts. Articles are the most dominant type of documents followed by conference papers, and review articles. Medicine is the most represented subject. CONCLUSION: Officials of the Ss Cyril and Methodius University of Skopje should undertake more effective and proactive policies for journal publishers and their Editorial Boards in order to include more journals from UC&M in the Scopus database.